Influence of eicosapentaenoic acid (20:5, n-3) on secretion of lipoproteins in CaCo-2 cells. - T Ranheim; A Gedde-Dahl; AC Rustan; CA Drevon (Journal of Lipid Research, 1992)
CaCo-2 cells, grown on filter membranes, were used to study the effects of fatty acids on cellular metabolism of triacylglycerol and phospholipids. The rate of triacylglycerol secretion was enhanced more than 2-fold, from 1 to 2 weeks after reaching confluency, in the presence of 0.6 mM fatty acids. Triacylglycerol secretion and oxidation of oleic acid increased 2- and 9-fold, respectively, with this culture system, as compared to cells grown on conventional plastic dishes. Eicosapentaenoic acid (20:5 n-3), when compared to oleic acid, did not reduce formation of triacylglycerol or enhance phospholipid synthesis in CaCo-2 cells during short term (less than 24 h) experiments, when the cells resided on membranes, regardless of what type of radioisotopes were used as precursors in the incubation media. However, the n-3 fatty acid was preferentially incorporated into phosphatidylinositol, lysophosphatidylcholine, and sphingomyelin, as compared to oleic acid. The disappearance from the apical medium and cellular uptake of labeled eicosapentaenoic and oleic acid were similar during incubations up to 24 h, and the metabolism of these fatty acids to acid-soluble materials and CO2 was equal. Light scattering analysis indicated that secreted lipoproteins of density less than 1.006 g/ml were in the same size-range as chylomicrons derived from human plasma. Assessment of secreted apolipoprotein B showed that by incubating CaCo-2 cells with oleic acid, apolipoprotein B levels increased approximately 1.4-fold when compared to cells incubated with eicosapentaenoic acid, whereas the amount of triacylglycerol and size-range of particles were similar for the two fatty acids. Our data indicate that CaCo-2 cells grown on filter membranes exhibit enterocyte-like characteristics with the ability to synthesize and secrete chylomicrons. Eicosapentaenoic acid and oleic acid are absorbed, metabolized, and influence secretion of lipoprotein particles in a similar way, except for some differences in incorporation of the fatty acids into certain phospholipid classes and a reduced secretion of apolipoprotein B. The culture conditions, including time after confluency and cellular support, are critical for the rate of secretion in the presence of eicosapentaenoic acid and oleic acid.